Implementation of Machine Learning Algorithms in Iot Smart Shoe Helping Rehabilitation for Visually Challenged People - Aparna S Hambarde, Shailesh M Hambarde, Chandraprabha A Manjare, Poonam D Lambhate, Sandip D Satav (Journal for ReAttach Therapy and Developmental Diversities, 2023)
People who really are visually challenged will benefit from this study, which aims to help them complete their daily chores. Traveling outside can be difficult for those who are blind or have low vision, but this article explores a solution that uses Internet of Things (IOT) to construct sensor that can be worn on shoes. To warn the user of impending danger, ir sensor and a siren are employed. Ultrasonic, a sensor array, and an Arduino board make up this IoT-based Intelligent shoe solution for the blind. There is a lot of focus on the Internet of Things these days. physical equipment and other objects, including humans, being linked together Despite the fact that the market for this technology has grown significantly, it is still being developed at an accelerated pace. When people move from one place to another, the biggest problem occurs. It's impossible for someone carrying a stick to be aware of everything that might be lurking in their path. When it comes to walking on your own, this clever shoe design is a long-term solution for blind people. The smart sneaker will help the vision impaired go to their destination on their own thanks to safety measures. Incorporating sensors, microcontrollers, and buzzers into the shoe's design, it is built using Internet of Things (IoT) technology. You'll be alerted as soon as you step into the shoe if it detects an impediment in your path. by making a buzzing noise and then. Incorporating IoT and sensors, smart glasses are becoming a reality. Additionally, it aids in the discovery of potential problems by considering a wider variety of potential problems. The By exchanging data with one another, the smart shoe keeps the wearer safe from hitting any impediments in his path. A safe and self-contained way for them to arrive at their goal